The Mid-Atlantic Shore to the Appalachian Highlands 2010
DOI: 10.1130/2010.0016(02)
|View full text |Cite
|
Sign up to set email alerts
|

Soils, geomorphology, landscape evolution, and land use in the Virginia Piedmont and Blue Ridge

Abstract: The object of this fi eld trip is to examine the geology, landforms, soils, and land use in the eastern Blue Ridge and western Piedmont geologic provinces in Orange County in central Virginia. A complex mix of igneous, sedimentary, and metamorphic bedrocks, ranging in age from Mesoproterozoic to Triassic (possibly some Jurassic) underlie the area. Soils are equally varied with a total of 62 series mapped in Orange County alone. The area being relatively stable tectonically, landforms generally refl ect the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…In general, landform variations may contribute to changes in soil properties (clay content), human activities (i.e., land use), vegetation quality and quantity, and alteration of climatic variables (temperature and precipitations), which may affect the SOC distribution. Similarly, a previous study reported that landform elements play a significant role in the variability of SOC [77]. Even though the variability of SOC depends on geologic, climatic, topographic, vegetation, and land-use variables, landform plays a crucial role in modifying all these factors.…”
Section: Soc Distribution Across the Landform Land Use And Lithologymentioning
confidence: 61%
“…In general, landform variations may contribute to changes in soil properties (clay content), human activities (i.e., land use), vegetation quality and quantity, and alteration of climatic variables (temperature and precipitations), which may affect the SOC distribution. Similarly, a previous study reported that landform elements play a significant role in the variability of SOC [77]. Even though the variability of SOC depends on geologic, climatic, topographic, vegetation, and land-use variables, landform plays a crucial role in modifying all these factors.…”
Section: Soc Distribution Across the Landform Land Use And Lithologymentioning
confidence: 61%
“…In general, the landform variations may contribute to changes in soil properties (clay content), human activities (i.e., land-use), and vegetation quality and quantity, alteration of climatic variables (temperature and precipitations) that may affect the SOC distribution. Similarly, previous studies reported that landform elements play a significant role in the variability of SOC [69,70]. Even though the variability of SOC depends on geologic and climatic, topographic, vegetation [32], and land-use variables [71], landform plays a crucial role in modifying all these factors [72].…”
Section: Influence Of Topographic and Vegetation Indicesmentioning
confidence: 64%
“…We investigated two sites on crystalline bedrock (Figure 1). The South Carolina Piedmont (SCP) site (436432E 3829851N Z17N) is in the Appalachian Piedmont and is underlain by igneous and metamorphic rocks (Pavich, 1989; Secor et al., 1986; Sherwood et al., 2010). The Blair Wallis (BW) site (327659E 3847004N Z13N) is on granitic rocks of the Sherman batholith, which has little to no foliation (Edwards & Frost, 2000; Eggler et al., 1969; Frost et al., 1999).…”
Section: Site Selectionmentioning
confidence: 99%